Lean Thinking : Banish Waste and Create Wealth in Your Corporation - Womack, James P. and Jones, Daniel T. (London Simon & Schuster, 1996)
If The Machine That Changed the World is a description of the Toyota system in the industry of its origin, Lean Thinking is a generalization of the basic concepts so they can be applied to any company in any industry. The authors begin by summarizing the five inherent principles in any lean system: 1 correctly specify value so you are providing what the customer actually wants, 2 identify the value stream for each product family and remove the wasted steps that don't create value but do create muda (waste), 3 make the remaining value-creating flow continuously to drastically shorten throughput times, 4 allow customer to pull value from your rapid-response value streams as needed (rather than pushing products toward the customer on the basis of forecasts), and 5 never relax until you reach perfection, which is the delivery of pure value instantaneously with zero muda. (The first part of Lean Thinking devotes a chapter to each of these principles.) In the second part, the authors describe in detail how managers in a wide range of companies and industries - small, medium and large, North American, European and Japanese - transformed their business by applying the principles of lean thinking. Chapters are devoted to Pratt and Whitney, Wiremold, Lantech in North America, Porsche in Germany, and Showa Manufacturing in Japan. Lean Thinking has sold more than 300,000 copies in the English language hard-cover version alone, because it's an indispensable companion for every manager making the lean journey.
Includes Illustrations, Notes, Glossary and Index.
Keywords: Organizational Effectiveness